Kepuasan Kerja Pegawai: Peran Kepemimpinan Transformasional, Work Life Balance dan Psychological Well Being - Abdil Tsabit Fadhila; Vivin Maharani Ekowati; Achmad Sani Supriyanto (DIALEKTIKA: Jurnal Ekonomi dan Ilmu Sosial, 2025)
The success of a organization in achieving its targets is highly dependent on the skills and abilities of its employees. HR is a key factor that drives all organizational activities. The purpose of this study is to examine and analyze the effect of transformational leadership and work-life balance on job satisfaction,  and testing psychological well-being as a mediator of the influence of transformational leadership and work-life balance on job satisfaction.. This study employs a quantitative approach using questionnaires distributed to employees. The population and sample used in this study consist of all employees, totaling 70 employees. The data analysis was conducted using the Structural Equation Modeling–Partial Least Square (SEM-PLS) method with the help of SmartPLS software. The results indicate that transformational leadership has a positive and significant effect on job satisfaction, while work-life balance does not have a positive and significant effect on job satisfaction. Furthermore, psychological well-being is proven to act as a mediating variable.